Exploring the impact of Kahoot! as a collaborative gamified mathematics learning platform for Jordanian junior school gifted students - AlAli, Rommel; Wardat, Yousef (Journal of Asian Scientific Research, 2024)
This research delves into the distinctive challenges faced by educators of gifted students in Jordan, specifically focusing on the intricacies of delivering compelling lectures that foster academic excellence. To tackle this challenge, the study explores the potential of integrating game elements into the educational framework, with a particular emphasis on harnessing the popular platform Kahoot! to enhance engagement and academic achievement among gifted students. The primary goal is to evaluate the effectiveness and enjoyment of Kahoot! as a learning approach for gifted students in Jordan. Employing a quantitative methodology, the research analyzes data from 112 gifted students actively involved in using Kahoot! as an integral part of their learning experience. The investigation aims to scrutinize Kahoot!’s impact on the academic achievements of gifted students while assessing the potential benefits associated with integrating gamification elements into pedagogical strategies. The findings significantly contribute to determining the suitability of Kahoot! as a teaching strategy that incorporates gamification elements, especially in enhancing the academic accomplishments of gifted students in Jordan. Furthermore, the study explores innovative solutions to engage gifted students by infusing gaming elements into the instructional process, providing valuable insights for broader applications of gamification techniques to enhance engagement, motivation, and knowledge retention among gifted students within the Jordanian educational landscape.